2013
DOI: 10.1371/journal.pone.0074882
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Pharmacy Staff Knowledge and Practice on Childhood Diarrhea Management in Vietnam: Are Educational Interventions Effective?

Abstract: BackgroundIn many developing countries, private pharmacies play an important role in providing health information and services to local communities for common health issues. The aim of this study was to ascertain medium-term impact of educational interventions on knowledge and practice of pharmacy staff regarding management of childhood diarrhea in Vietnam.MethodsThis was a pre- and post-intervention study with 32 and 44 months difference from the time of the baseline survey to the conclusion of trainings and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 26 publications
6
31
0
2
Order By: Relevance
“…In Vietnam, an average duration of 2.4-2.6 minutes for consultations regarding childhood diarrhea was reported by pharmacists. The study concluded that the time spent for consultation was insufficient to assess the condition of childhood diarrhea [13]. The number of questions asked regarding the condition of the child by the pharmacists was low.…”
Section: Consultation On History Of the Illnessmentioning
confidence: 97%
See 3 more Smart Citations
“…In Vietnam, an average duration of 2.4-2.6 minutes for consultations regarding childhood diarrhea was reported by pharmacists. The study concluded that the time spent for consultation was insufficient to assess the condition of childhood diarrhea [13]. The number of questions asked regarding the condition of the child by the pharmacists was low.…”
Section: Consultation On History Of the Illnessmentioning
confidence: 97%
“…Several studies in low-and middle-income countries have reported a lack of adherence to treatment guidelines for diarrhea as well as an overuse of antibiotics and antimotility drugs among qualified practitioners [9,13,18]. In these settings, it is possible that pharmacy staff is not even aware of such guidelines, given that 88% of staff manning pharmacies on a day-to-day basis is unqualified [17].…”
Section: Adherence To Treatment Guidelinesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies focused on CE programs for the management of major chronic illnesses, such as asthma, depression, and diabetes, used live media methods (e.g., workshops, lectures, and case studies), and were performed in developed countries (Rouleau, Beauchesne, Laurier, 2007;Saini et al, 2006;Chen et al, 2004;Pham et al, 2013). The differences between minor ailments and major chronic illness, between Internet-based and live media methods, and between pharmacy education curricula in developing and developed countries do not permit extrapolation of published data to our area of interest.…”
Section: Introductionmentioning
confidence: 99%